2006
DOI: 10.1038/sj.leu.2404439
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair contributes to the drug-resistant phenotype of primary acute myeloid leukaemia cells with FLT3 internal tandem duplications and is reversed by the FLT3 inhibitor PKC412

Abstract: The presence of internal tandem duplications (ITD) mutations in the FMS-like tyrosine kinase 3 (FLT3) receptor influences the risk of relapse in acute myeloid leukaemia (AML). We have investigated DNA repair in FLT3-ITD and wild-type (WT) cells. Using the comet assay, we have demonstrated that the FLT3 inhibitor PKC412 significantly inhibits repair of DNA damage in the MV4-11-FLT3-ITD cell line and FLT3-ITD patient samples but not in the HL-60-FLT3-WT cell line or FLT3-WT patient samples. Following the discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 27 publications
(33 reference statements)
5
67
0
Order By: Relevance
“…It is likely that higher levels of FLT3-ITD might trigger pathways involved in chemoresistance more intensively, for example by enhancing DNA repair and salvage of damaged cells. 36 Our observations confirm the importance of the FLT3-ITD/FLT3 ratio, representing the FLT3-ITD allelic burden, with regards to prognosis and demonstrate that WBC count is not a surrogate marker for the FLT3-ITD/FLT3 ratio, but indeed is an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 79%
“…It is likely that higher levels of FLT3-ITD might trigger pathways involved in chemoresistance more intensively, for example by enhancing DNA repair and salvage of damaged cells. 36 Our observations confirm the importance of the FLT3-ITD/FLT3 ratio, representing the FLT3-ITD allelic burden, with regards to prognosis and demonstrate that WBC count is not a surrogate marker for the FLT3-ITD/FLT3 ratio, but indeed is an independent prognostic factor.…”
Section: Discussionsupporting
confidence: 79%
“…FLT3-ITD was demonstrated to activate alternative unfaithful DNA repair pathways that leads to increased levels of unrepaired DNA damage (22). Interestingly, it was also shown that increased efficiency of FLT3-ITDstimulated DNA repair contributes to drug resistance (23).…”
mentioning
confidence: 99%
“…In addition to the well-known role of p53 in apoptosis induction, it has also been shown to induce multiple prosurvival and DNA repair genes (26). Consistent with this, FLT3-ITD-expressing AML cell lines and primary patient samples have increased the levels of reactive oxygen species, double-strand DNA breaks and increased DNA repair capacity (17,27).…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, DNA repair contributes to the FLT3-ITD drug-resistant phenotype of primary AML (17). Several studies demonstrate drug resistance conferred by FLT3-ITD (16,18,19); however, thus far, no studies have demonstrated the effect of mutations in the FLT3 TKD on anticancer drug resistance.…”
Section: Introductionmentioning
confidence: 99%